Obscure oases: natural, cultural and historical geography of western Queensland's Tertiary sandstone springs. (20th January 2016) - Silcock, Jennifer L.; Macdermott, Harry; Laffineur, Boris; Fensham, Roderick J.
Abstract: The distribution of surface water dictates human and animal activity in arid zones. Although typically small, hidden, and inaccessible, springs and wells fed by local aquifers were the only sources of reliable water across vast areas of inland Australia until the last century. Compared to larger, more accessible water sources such as riverine waterholes and Great Artesian Basin discharge springs, their history is sketchy and poorly documented, although rich in intrigue and mythology. Since the expansion of artificial waters and motorised transport, many of these small oases have been forgotten, and their location and permanence are now less well‐known than for thousands of years. We examine the distribution, hydrogeology, cultural history, and biological values of Tertiary sandstone springs in western Queensland based on a review of historical literature, interviews with long‐term residents, and extensive field surveys. One hundred and sixty springs were documented, and nearly 40% of these have declined in flow or become inactive since pastoral settlement for reasons that are not well understood. While their decline in some areas seems related to shallow bores sunk into their local aquifers, it is possible that some smaller springs owed their existence to regular human maintenance. Others are probably naturally dynamic over decadal time scales. This study documents an almost‐forgotten aspect of Queensland's natural and cultural history.